Diagnostic Salivary Biomarkers in Traumatic Brain Injury: Narrative Review - Shahideh Rostami; Fatemeh Heidarzadeh; Sara Ashourzadeh Fallah; Seyed Alireza Rahimi; Maryam Mehrizi; Fatemeh Sadeghi; MohammadHossein Shahrabadi; Marziyeh Hajizadeh; Jennifer Swann; Alireza Jalali Farahani; Seyed Morteza Hosseiniara (Novelty in Clinical Medicine, 2022)
Traumatic brain injury (TBI) is a common cause of disability and mortality worldwide. TBI is an acquired brain injury that may be open (penetrating) or closed (non-penetrating) and is be categorized as mild, moderate, or severe, depending on the clinical presentation. Accurate diagnosis at the earliest stages can significantly affect patient discomfort, prognosis, therapeutic intervention, survival rates and recurrence. Whereas traditional CT and MRI techniques for diagnosis are dominant in clinical situations, a promising direction for clinical diagnosis is the use of fluid biomarkers like blood, CSF, urine, and saliva. Fluid biomarkers that may track these injuries and inflammatory processes have been explored for their potential to provide objective measures in TBI assessment. At present, there are limited clinical guidelines available regarding the use of fluid biomarkers in TBI. In recent years, saliva has received significant attention as a biomarker for TBI in clinical practice due to the non-invasive accessibility, cost-effective collection, and consistent relationship with serum. This review examines the utility of saliva biomarkers such as S100B, noncoding RNAs (ncRNAs), extracellular vesicles (EVs), miRNAs levels, microtubule-associated protein tau, alpha-amylase, cortisol, and oxidative stress in TBI. The study highlights the current state of salivary diagnostics, future aspirations, and their potential as the preferred route of TBI detection. The newly developed techniques for salivary analysis of these molecules may help to improve outcomes for TBI through rapid detection current unavailable with serum samples. Future studies via salivary biomarkers will help establish consistent strategies for early diagnosis of TBI and improve treatment outcomes of TBI patients.